From Calcium to Cadmium: Testing the Pairing Functional through Charge Radii Measurements of Cd 100-130 - Hammen, M.; Noertershaeuser, W.; Balabanski, D. L.; Bissell, M. L.; Blaum, K.; Budincevic, I.; Cheal, Bradley; Flanagan, K. T.; Froemmgen, N.; Georgiev, Georgi; Geppert, Ch.; Kowalska, M.; et al. (Physical Review Letters, 2018)
Differences in mean-square nuclear charge radii of Cd100-130 are extracted from high-resolution collinear laser spectroscopy of the 5s S21/2→5p P23/2 transition of the ion and from the 5s5p P32→5s6s S31 transition in atomic Cd. The radii show a smooth parabolic behavior on top of a linear trend and a regular odd-even staggering across the almost complete sdgh shell. They serve as a first test for a recently established new Fayans functional and show a remarkably good agreement in the trend as well as in the total nuclear charge radius.
CRIS-Team Scopus Importer:2021-07-19